2001
DOI: 10.1557/proc-687-b9.6
|View full text |Cite
|
Sign up to set email alerts
|

A Constitutive Model for the Mechanical Behavior of Single Crystal Silicon at Elevated Temperature

Abstract: Abstract--Silicon in single crystal form has been the material of choice for the first demonstration of the MIT microengine project. However, because it has a relatively low melting temperature, silicon is not an ideal material for the intended operational environment of high temperature and stress. In addition, preliminary work indicates that single crystal silicon has a tendency to undergo localized deformation by slip band formation. Thus it is critical to obtain a better understanding of the mechanical beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Although mono-crystalline silicon is often considered brittle, plastic deformation is known to occur [52]. Plastic deformation of the silicon most likely happens during cool down between approximately 630 • C and 970 • C. This region is above the britle-to-ductile transition temperature of silicon [53] and below the viscous flow point of silicon dioxide [54], [55]. However, we have no data to confirm this.…”
Section: Discussionmentioning
confidence: 84%
“…Although mono-crystalline silicon is often considered brittle, plastic deformation is known to occur [52]. Plastic deformation of the silicon most likely happens during cool down between approximately 630 • C and 970 • C. This region is above the britle-to-ductile transition temperature of silicon [53] and below the viscous flow point of silicon dioxide [54], [55]. However, we have no data to confirm this.…”
Section: Discussionmentioning
confidence: 84%
“…In low-C steel, numerous investigations have been performed on the yield point phenomenon, [35][36][37] and the stress concentration was observed to have a strong influence on the Lu¨ders band. [37][38][39][40] Several studies assessed the microstructural origin of the Lu¨ders band propagation, [41][42][43][44] and others proposed the thermal effects associated with strain localization. [45][46][47] Dissipative thermal effects due to the Lu¨ders band propagation were observed by means of infrared image processing, for a S355MC steel grade (0.5C0.35Mn), and a low-amplitude thermal front of 2°C or 3°C was reported.…”
Section: Bh Of the Isolated Ferrite And Bainite Constituentsmentioning
confidence: 99%
“…10 shows stress-strain curves for Si at various levels of initial dislocation density. Measurements of the upper yield strength of Si [23], [24] have also shown that the upper yield strength of Si is a function of temperature, strain rate, and initial density of dislocations. The key question is whether or not the structural design of Si-SiC hybrid structures can rely on the upper yield strength of Si, which has been adopted for the allowable stress in the analysis so far.…”
Section: Materials and Structures Issues In The Design Of Si-sic Hmentioning
confidence: 99%
“…The model developed for this purpose is described elsewhere [23]- [25]. It consists of a continuum description of the plasticity of silicon, with nominal dislocation density and shear resistance as the internal variables.…”
Section: Materials and Structures Issues In The Design Of Si-sic Hmentioning
confidence: 99%
See 1 more Smart Citation